2001
DOI: 10.1136/ard.60.10.934
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity and lifestyle, reproductive factors, and environmental exposures associated with rheumatoid arthritis

Abstract: Objective-To evaluate the influence of lifestyle, reproduction, and some external factors on the development of rheumatoid arthritis (RA) and to describe its comorbidity. Methods-Cases were identified retrospectively from 1980 to 1995 at the University Hospital in Linköping, Sweden. The study comprised 422 cases and 859 randomly selected population referents. Data on possible aetiological factors and comorbidity were collected by postal questionnaire. Results-The response rates were 67% among cases and 59% amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(37 citation statements)
references
References 32 publications
1
36
0
Order By: Relevance
“…Smoking rates of ever, current and past were 50.6%, 26.5% and 26.3%, respectively. In the 11 case–control studies,8 9 11 12 18 19 20 21 22 34 35 36 4764 cases and 13 647 controls were included, and in five cohort studies,5 7 10 37 38 9121 cases were identified from among 566 044 participants. Seven case–control studies and one cohort study of male subjects and nine case–control and five cohort studies of female subjects were included.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Smoking rates of ever, current and past were 50.6%, 26.5% and 26.3%, respectively. In the 11 case–control studies,8 9 11 12 18 19 20 21 22 34 35 36 4764 cases and 13 647 controls were included, and in five cohort studies,5 7 10 37 38 9121 cases were identified from among 566 044 participants. Seven case–control studies and one cohort study of male subjects and nine case–control and five cohort studies of female subjects were included.…”
Section: Resultsmentioning
confidence: 99%
“…In the seven case–control studies11 18 19 20 21 22 35 36 the summary OR for ever, current and past smokers were 1.87 (1.53 to 2.29), 1.89 (1.49 to 2.40) and 1.79 (1.34 to 2.38). Differences in smoking status were not significant.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This seems to be in contrast to our results in which diabetes prevention was associated with a decrease in Lactobacillus spp. While allergies and IBD are characterized by Th2 responses, T1D is associated with Th1 immune responses [41]. Interestingly, neonatal antibiotic treatment may skew the Th1 immune response towards a Th2 profile, an effect that can be reduced by supplementation of Gram-positive, microaerophilic bacteria [42].…”
Section: Discussionmentioning
confidence: 99%
“…A dose-response gradient, however, has been suggested in three studies (82,84,87). Such a monotonic relation between exposure and outcome supports causality, but its absence is not falsifying.…”
Section: Smokingmentioning
confidence: 85%